Comparing C-tests and Yes/No vocabulary size tests as predictors of receptive language skills. (October 2016) - Harsch, Claudia; Hartig, Johannes
Placement and screening tests serve important functions, not only with regard to placing learners at appropriate levels of language courses but also with a view to maximizing the effectiveness of administering test batteries. We examined two widely reported formats suitable for these purposes, the discrete decontextualized Yes/No vocabulary test and the embedded contextualized C-test format, in order to determine which format can explain more variance in measures of listening and reading comprehension. Our data stem from a large-scale assessment with over 3000 students in the German secondary educational context; the four measures relevant to our study were administered to a subsample of 559 students. Using regression analysis on observed scores and SEM on a latent level, we found that the C-test outperforms the Yes/No format in both methodological approaches. The contextualized nature of the C-test seems to be able to explain large amounts of variance in measures of receptive language skills. The C-test, being a reliable, economical and robust measure, appears to be an ideal candidate for placement and screening purposes. In a side-line of our study, we also explored different scoring approaches for the Yes–No format. We found that using the hit rate and the false-alarm rate as two separate indicators yielded the most reliable results. These indicators can be interpreted as measures for vocabulary breadth and as guessing factors respectively, and they allow controlling for guessing.